Dennis Brabazon in his boat, The Joke, in which he rowed from Albury to the mouth of the Murray, New South Wales, 1924 - Burton, Albert (1924)
Dennis Brabazon, originally from near Glenrowan, Victoria, rowed down the Murray River from Albury in 1924 and kept a diary of his trip and developed his photographs as he went. Albert Burton was a friend of Brabazon and accompanied him for part of the journey down the Murray River.
Title based on information in Great Australian book of nostalgia / John Larkins and Bruce Howard.
Part of the collection: Nostalgic Australian photographs.
Part of the Bruce Howard collection.
Published in: Great Australian book of nostalgia / John Larkins and Bruce Howard, Adelaide : Rigby, 1975, p. 69.
Also available online
Keywords: Brabazon, Dennis -- Portraits; Boatsand boating -- New South Wales -- Albury Region -- Photographs; Albury Region (N.S.W.) -- Photographs